Perception and attitude of general practitioners regarding generic medicines in Karachi, Pakistan: A questionnaire based study - Jamshed, Shazia Qasim; Mohamed Ibrahim, Mohamed Izham; Ahmad Hassali, Mohamed Azmi; Masood, Imran; Low, Bee Yean; Shafie, Asrul Akmal; Babar, Zaheer-ud-din (BioMed Central, 2012)
Objectives: In developing countries out-of-pocket payments (OOP) are as high as 80% of healthcare spending. Generic medicines can be instrumental in reducing this expenditure. The current study is aimed to explore the knowledge, perception, and attitude of general practitioners towards generic medicines in Karachi, Pakistan.